Bioactive compounds, antioxidant and physic-chemical characteristics of the dovyalis fruit - Maria Cristina Copello Rotili; Fabíola Villa; Gilberto Costa Braga; Daiane Luckmann Balbinotti de França; Solivan Rosanelli; Jessica Cristina Urbanski Laureth; Daniel Fernandes da Silva (Acta Scientiarum. Agronomy, 2018)
The objective of this work was to evaluate the bioactive compounds, antioxidant activity, and physicochemical characteristics of dovyalis fruit to obtain technological knowledge about this fruit when grown under the conditions found in the municipality of Marechal Cândido Rondon, Paraná State, Brazil. Dovyalis fruits from the State University of Western Parana, which was established in 2012, were harvested in March 2016. Dovyalis fruits were collected from several plants and were divided among three lots. After the harvest, were immediately taken to the Post-Harvest Laboratory for evaluation of the antioxidant activity by the DPPH, ABTS and FRAP methods. The physicochemical characteristics of the fruits and the total phenolic compounds, flavonoids, ascorbic acid, anthocyanins, respiration, and fruit color were evaluated. The experimental design was completely randomized, with the study containing three groups and three replicates per group. Dovyalis fruits present high antioxidant capacity and are characterized as acidic fruits, due to the high FRAP activity. Dovyalis fruits have a very attractive color and high acidity, which makes them appropriate for processing. Regarding the antioxidant activity present in the fruit, the most bioactive components are flavonoids and anthocyanins. High ascorbic acid content was observed in mature dovyalis fruits. Dovyalis fruits are considered climacteric.